Notary Role in The Establishment of Foreign Investment Limited Company Based on The Act No. 25 Of 2007 on Investment in Semarang - Noor Rachmawati; Lathifah Hanim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Research on the role of the notary in the establishment of a Foreign Investment Limited Company (PMA) in Semarang aims to determine the role of a notary in the establishment PT.PMA. The research method is normative with library research and regulatory legislation in the field of investment include field research. This study uses a technique of direct communication with the tool in the form of interview guidelines. Interviews are used is free unstructured but questions that do not come out of the subject matter. Based on the results of the study concluded that the role of the notary in the establishment of PT. PMA is based on Act No. 25 of 2007 on Investment in Semarang are procedures that should be implemented is the submission of PMA addressed to the Investment Coordinating Board (BKPM), with regard to this case, the task of the notary help the government provide legal counseling for the parties to the establishment, make Joint Venture Agreement in accordance with applicable legislation and in charge of manufacture of a limited liability company's certificate of incorporation approved by the Minister of Justice and Human Rights of the Republic of Indonesia. In the event of an error PT.PMA establishment, the notary is responsible for the deed change, but the responsibility of the notary in the case of the fraud perpetrated by the founder of the company who act in bad faith, then it becomes the responsibility of the founders of the company. Constraints faced by thebusiness licensing constraints, constraints business domicile, the determination of business areas, administrative requirements and constraints lack of capital to start build a company.Keywords: Role of the Notary; Foreign Investment; Limited Company.